ANALISA KEBOCORAN SAMBUNGAN LAS PIPA SANITARY SS 316L YANG DI RENDAM DALAM LARUTAN PH 4 - Oktariady, Muhammad; M. Rasid; Ella Sundari (MACHINERY Jurnal Teknologi Terapan, 2025)
This study aims to analyze the cause of leakage in SS 316L sanitary pipes used for food additive distribution. The leakage is suspected to be caused by corrosion due to exposure to the acidic environment. The research was conducted experimentally using 12 samples subjected to different treatments: no welding, argon welding, and electric welding using NSN-309L/E 309-16 and NSN-316/E 309-16 electrodes. All samples were immersed for 24 hours in a pH 4 solution and tested using the gravimetric method to measure mass loss due to erosion. The results showed that pH 4 acid solution significantly caused mass reduction in the pipes, with the highest erosion occurring in electric welding joints. The highest erosion percentage, 2.99%, was found in samples welded with NSN-309L/E 309-16 electrodes, while unwelded samples experienced only 0.21% erosion. The validity of the data was tested and confirmed based on the comparison between the calculated r-value and the critical r-table value. The conclusion indicates that the welding method influences the pipe’s susceptibility to corrosion, with electric welding posing a higher risk than argon welding in acidic environments.